Specification of Robots for the Treatment of Autistic Children - Valença, Thauanne Santana Fonseca; Carvalho, Elyson Ádan Nunes; Freire, Eduardo Oliveira; Molina, Lucas; Carvalho Filho, José Gilmar Nunes de (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
In this paper, we present a study on the use of robots in autistic children’s treatment. In therapeutic approaches to autistic children, socially assistive robotics (SAR) has been used to stimulate the cognitive abilities of them, respecting their limitations. From interviews with health professionals and by attending therapeutic consultations, we defined four examples of activities that the robot could perform in Analysis Behavior Applied (ABA) therapies using the triad of interaction. In this way, we proposed the desired characteristics of the robot and defined its functionalities for the use in the treatment of autistic children, both in ABA therapies and school environments.